Agrarian West Bengal : three field studies - Gupta, Ranjit Kumar, 1920- (Institute of Social Research & Applied Anthropology, Deptt. of Anthropology, Calcutta University : distributors, Subarnarekha, 1977)
On socioeconomic conditions of the rural poor; field studies undertaken during 1975-1976 in three agricultural areas, Moyna, Bagri Pargana, and Susnia in West Bengal.